1989
DOI: 10.2190/npea-2j32-5cv3-rug7
|View full text |Cite
|
Sign up to set email alerts
|

Older Widows and Married Women: Their Intimates and Confidants

Abstract: Interview data obtained from 132 women sixty-five and older reveals that the widows and married women have a comparable number of primary friends. Being over age seventy-four influences the size of the friendship network for widows but not married women. The primary friendships of widows and married women parallel each other in terms of endurance and stability. Primary ties with men are the exception rather than the norm, for both widows and married women. Widows do differ from married women in that the former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…This is not to say that certain hyper-masculine behaviors did not associate women with lesbianism (Griffin 1998;Worthen 2014), but that women were given more leeway for emotional expression than men. This freedom of expression is more closely associated with young women, as research has shown a decline in the closeness between women who are married (Babchuk and Anderson 1989). Indeed, powerful patriarchal forces have sought to limit the closeness of adult female friendships, as they pose a threat to the strength of male alliances and patriarchal rule (Sedgwick 2015).…”
Section: The Influence Of Homohysteria On Homosocialitymentioning
confidence: 99%
“…This is not to say that certain hyper-masculine behaviors did not associate women with lesbianism (Griffin 1998;Worthen 2014), but that women were given more leeway for emotional expression than men. This freedom of expression is more closely associated with young women, as research has shown a decline in the closeness between women who are married (Babchuk and Anderson 1989). Indeed, powerful patriarchal forces have sought to limit the closeness of adult female friendships, as they pose a threat to the strength of male alliances and patriarchal rule (Sedgwick 2015).…”
Section: The Influence Of Homohysteria On Homosocialitymentioning
confidence: 99%
“…Not only during childhood, but throughout the life span, reciprocity is a central characteristic of friendships (Patterson & Bettini, 1993). For example, individuals with disabilities attempt to maintain reciprocal supportive relationships (Antonucci & Jackson, 1990), working-class women have friendships that are very reciprocal with respect to goods and services (Walker, 1995), and the relationships between older women and their confidants are characterized by norms of reciprocity (Babchuk & Anderson, 1989) as well as by actual reciprocity in the exchange of various resources (Blieszner, 1993). Reciprocity may be particularly important when it concerns the giving and receiving of support.…”
Section: Reciprocity and Loneliness In Friendshipsmentioning
confidence: 99%
“…In a nursing home, greater lucidity and better vision and speech are associated with having more friends (Retsinas & Garrity, 1985). Among community-dwelling older adults, elderly women have more friends than do elderly men (Fischer & Oliker, 1983), women in age-segregated housing have more friends than do those living elsewhere (Adams, 1983), employed women have more friends than do other older women (Babchuk & Anderson, 1989), and participants in social activities have more friends than do nonparticipants (Spakes, 1979). Older widows have fewer friends than younger ones, but the number of married women's friends does not differ by age (Babchuk & Anderson, 1989).…”
Section: Dimensions Of Personal Relationshipsmentioning
confidence: 99%